Examining the Phenomenon of Code Switching in the Language of Recidivists - Uricska, Erna (Magyar Rendészet, 2015)
As with every specialty, police have their own use of subject jargon and special terminology. The language of the police is a combination of punctual, administrative gobbledygook which aims to be economical, efficient and necessary for their work. This kind of language also combines the special vocabulary of the different social groups in the criminal underworld. This work aims to show how this special, code-mixed combination of language appears in use in recidivists’ vocabulary examining the characteristics of the so called code-switching.